Implementasi Buku Mutaba'ah GATOTKACA dalam Pembentukan Karakter Religius dan Peningkatan Prestasi Murid di MIN 2 Sukoharjo: Kajian Konseptual dan Teoritis - Priyanto Priyanto; Joko Subando (Lembaga Yasin AlSys, 2026)
The implementation of the mutaba’ah book in Islamic education is one relevant habituation strategy for forming religious character and supporting the improvement of students’ achievement. However, conceptual studies that specifically discuss the GATOTKACA Mutaba’ah Book as an instrument for monitoring students’ activities at home remain limited. This study aims to conceptually and theoretically examine the implementation of the GATOTKACA Mutaba’ah Book at MIN 2 Sukoharjo as an instrument for forming religious character and improving students’ achievement. The GATOTKACA Mutaba’ah Book is an acronym for Gerakan Membatasi Menonton Televisi dan Bermain Gawai dengan Mengembangkan Budaya Membaca, which is designed to monitor daily worship, reading activities, and restrictions on the use of electronic media. This study used a literature study approach by analyzing implementation theory, the concept of the mutaba’ah book in Islamic education, religious character, learning achievement, and habituation. The results of the review show that the implementation of the GATOTKACA Mutaba’ah Book has the potential to become an effective instrument for forming students’ religious character through structured and documented worship habituation, improving learning achievement through the strengthening of discipline and time management, and building two-way communication between the madrasah and parents. The success of its implementation is determined by careful planning, resource support, clarity of rules and policies, and synergy among teachers, students, and parents. This review contributes theoretically to the development of a habituation-based character education model in Madrasah Ibtidaiyah. Its implications emphasize the importance of a structured, collaborative monitoring instrument oriented toward strengthening religious culture, literacy, and control over the use of electronic media in supporting students’ character development and achievement.